Carbon Dioxide Conversion into Liquid Fuels by Hydrogenation and Photoelectrochemical Reduction: Project Description and Preliminary Experimental Results. (July 2017) - Pettinau, Alberto; Mureddu, Mauro; Ferrara, Francesca
Abstract: The increasing attention toward climate changes and the recent strategic policies to stabilize and reduce CO2 emission is promoting research in the field of carbon capture, storage and more recently utilization technologies, whereby CO2 is captured from industrial flue gas, reused if possible or permanently stored in geological formations, such as depleted oil or gas fields and saline aquifers. In this scenario, Sotacarbo is leading the "Centre of Excellence on Clean Energy" research project, funded by the Regional Government of Sardinia, which aims to develop technologies for low emission power generation and for CO2 capture, utilization and storage. Among these technologies, CO2 utilization by hydrogenation and photoelectrochemical reduction are experimentally studied in the Sotacarbo laboratories. This work presents a general overview of the researches (carried out in close cooperation with the University of Cagliari) on CO2 utilization by conversion into liquid fuels, with a description of the research facilities and a hint on preliminary experimental results.